2015
DOI: 10.3390/met5042021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Rolling on the Hydrogen Desorption Behavior of Binary Metal Hydride Powders under Microwave Irradiation

Abstract: In this paper we report that cold rolling could drastically improve hydrogen desorption kinetics under microwave irradiation. Samples of metal hydride powders (TiH2, ZrH2, and MgH2) in as-received conditions and after cold rolling were microwave irradiated in a vacuum using a simple experimental setup. After irradiation, the samples were characterized by X-ray diffraction in other to evaluate the effectiveness of microwave heating. The diffraction patterns indicated that only MgH2 could be fully decomposed (de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Depending on the dielectric properties of materials, the interaction of charged particles or polar molecules with the electric field part of the electromagnetic produces radiation heat . Several investigations have been carried out on the possibility of using such effects to drive the hydrogen desorption process and the effectiveness of microwave radiation varies as function of the hydrides. For example, no temperature increase was observed for simple ionic hydrides (LiH, NaH, MgH 2 and CaH 2 ) while metallic hydrides such as TiH 2 is heated to 327 °C upon a 3.5 min microwave irradiation .…”
Section: Non‐thermal and Non‐straightforward Thermally Driven Methodsmentioning
confidence: 99%
“…Depending on the dielectric properties of materials, the interaction of charged particles or polar molecules with the electric field part of the electromagnetic produces radiation heat . Several investigations have been carried out on the possibility of using such effects to drive the hydrogen desorption process and the effectiveness of microwave radiation varies as function of the hydrides. For example, no temperature increase was observed for simple ionic hydrides (LiH, NaH, MgH 2 and CaH 2 ) while metallic hydrides such as TiH 2 is heated to 327 °C upon a 3.5 min microwave irradiation .…”
Section: Non‐thermal and Non‐straightforward Thermally Driven Methodsmentioning
confidence: 99%
“…Dupim et al have shown that for MgH 2 , TiH 2 , and ZrH 2 , cold rolling enhance the microwave-assisted desorption. 69)…”
Section: Pure Magnesium and Commercial Mg Alloysmentioning
confidence: 99%
“…To improve the properties of magnesium hydride and other metal hydrides, mechanical methods are used [10][11][12][13]. Ball milling is one of the most common methods for removing the oxide layer from the magnesium particle surface leading to particle size reduction.…”
Section: Of 14mentioning
confidence: 99%